Strengthening the Value of Pancasila in Elementary Schools in Online Learning Through Whatsapp Group Media - Maulidayani, Tiana; Muktiarni, M; Mupita, Jonah (Indonesian Journal of Multidiciplinary Research, 2022)
Pancasila is a formulation and guideline in the life of the nation and state for the people of all Indonesia. In applying the values in Pancasila, this can be done in various ways such as using a media application called WhatsApp. Material on Pancasila will be given in the group so that students can easily gain knowledge about the values contained in Pancasila.Â  "Reading is fundamental for a person to gain another ability. However, there are still areas in Indonesia that still do not read. The aim of the core research is to provide innovation in literacy learning in grade 4 primary school. The study was conducted during a pandemic with an online learning system. . Students are given learning with sticky notes, where sticky notes are used as a medium. Sticky notes contain questions that must be matched with other sticky notes based on the same color. From the description above, we use this approach to test literature and theories so that they can fit the circumstances of the location we are researching. This is the basis for us to use a quantitative approach. The quantitative approach in this study was to determine the extent of the implementation of learning with Sticky Notes was to increase grade 4 students' reading interest in textbooks during the covid-19 pandemic. This approach emphasizes finding data to be processed systematically and using mathematical calculations. From the results of the study get an increase owned by students.